Leaf phenolics and pigments along with their antioxidative potential in some medicinal plants - Islam, Rumana; Injamum-Ul-Hoque, Md; Ashrafuzzaman, Md; Uddin, Md Nesar (Asian-Australasian Journal of Food Safety and Security, 2018)
Medicinal plants play significant role in human health. Besides this all of the Unani, Herbal, Kobiraji, and Homeopath medicine are produced from medicinal plant. The aim of the present study was to evaluate the phytochemical constituents as total phenolics content, free radical scavenging capacity, chlorophyll a, chlorophyll b, total chlorophyll (a+b) and carotenoids. Leaves of seven important non-solanaceous medicinal plants namely Boerhavia diffusa (punarnava), Adhatoda vasica (basok), Paederia foetida (gandhabhaduli), Rauwolfia serpentina (sarpogandha), Catharanthus roseus (pink nayantara), Catharanthus alba (white nayantara) and Andrographis paniculata (kalomegh) were extracted for phenolics, chlorophyll a and b as well as carotenoids in this experiment. Total phenolics content in seven medicinal plants in this experiment ranged from 142.44 (C. roseus) to 416.25 (A. vasica) mg GAE/100 g leaf fresh weight. The IC50 value for scavenging 2, 2- diphenyl-1- picrylhydrazyl (DPPH) free radicals ranged from 32.12 (C. roseus) to 38.40 (Boerhavia diffusa) mg mL-1 leaf extract in seven different medicinal plants. Pigments content such as chlorophyll a, chlorophyll b, chlorophyll (a+b) and carotenoids were found highest in Adhatoda vasica leaf as 2.347, 0.900, 3.283, and 0.521 mg g-1 fresh weight, respectively, among all the seven species. We may get highly valuable medicine from Adhatoda vasica (basok) leaf for its superior biochemical constituents, which will help our next generation to treat chronic diseases. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 86-92